Pengembangan LKM Model PBLberbasis Potensi Lokal pada Mata Kuliah Bioteknologi untuk Meningkatkan Kemampuan Berpikir Kritis Mahasiswa Di Universitas Muhammadiyah Kupang - LESTARI, NURDIYAH; SUDARISMAN, SUCIATI; SUGIYARTO, SUGIYARTO (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2014)
The purposes of this research were: 1) development of students worksheet Problem Based Learning (PBL) based on Local Potential; 2) test feasibility of the PBL model; 3) determine the effectiveness of PBL model. Analysis of the data used for research and development are qualitative and quantitative descriptive analysis, as well as the percentage techniques. Research and development of PBL models based on local potential uses 4-D model. The results of research and development showed: 1) product of PBL-based models are developed based on the stages of the Local Potential PBL syntax that uses indicators of critical thinking skills, 2) feasibility of the model PBL-based Local Potential according to experts is very well qualified with average of 92,1 %, qualified by education practition is very well with average of 94,5 %, whereas according to qualified students an excellent with average of 88,2 %; 3) student’s worksheet PBL-based Local Potential effectively improve critical thinking skills and learning results with gain value 9 and N-gain value 0.28 at low category. Based on result of t scores obtainable gain value 9.06 and N-gain value 0.420 at medium category.